Research and development efforts on texturization to reduce the optical losses at front surface of silicon solar cell. (December 2016) - Abdullah, M.F.; Alghoul, M.A.; Naser, Hameed; Asim, Nilofar; Ahmadi, Shideh; Yatim, B.; Sopian, K.
Abstract: Silicon wafer-based solar cell contributes to about 92% of the total production of photovoltaic cells. An average of 30% of the incident light is lost via reflection from the front surface of the silicon solar cell, thus reducing the cell's power conversion efficiency. Texturization is a process of producing the desired unevenness on the surface of solar cell. It is well known as a practical solution to the limitation. Front surface texture reduces cell reflectivity and contributes to more photocurrent generation within active materials. The research and development efforts to reduce the optical losses via texturization are reviewed in this paper. The mechanisms of optical loss reduction, desirable texture feature, methods of texturization, side effects of texturization, and its compatibility with other optical enhancements for crystal silicon cell are elaborated upon. Front surface texture is associated with minimizing optical loss, and negatively affecting carrier and electrical losses. The importance of texturization for crystalline silicon is briefly related with thin film amorphous silicon solar cell to fully encompass this topic. Lesson learned and conclusion is highlighted in the last section.